High levels of PAH-metabolites in urine of e-waste recycling workers from Agbogbloshie, Ghana - Feldt, Torsten; Fobil, Julius N.; Wittsiepe, Juergen; Wilhelm, Michael; Till, Holger; Zoufaly, Alexander; Burchard, Gerd; Göen, Thomas (Science of the Total Environment, 2014)
The informal recycling of electronic waste (e-waste) is an emerging source of environmental pollution in Africa. Among other toxins, polycyclic aromatic hydrocarbons (PAHs) are a major health concern for exposed individuals. In a cross-sectional study, the levels of PAH metabolites in the urine of individuals working on one of the largest e-waste recycling sites of Africa, and in controls from a suburb of Accra without direct exposure to e-waste recycling activities, were investigated. Socioeconomic data, basic health data and urine samples were collected from 72 exposed individuals and 40 controls. In the urine samples, concentrations of the hydroxylate PAH metabolites (OH-PAH) 1-hydroxyphenanthrene (1-OH-phenanthrene), the sum of 2- and 9-hydroxyphenanthrene (2-/9-OH-phenanthrene), 3-hydroxyphenanthrene (3-OH-phenanthrene), 4-hydroxyphenanthrene (4-OH-phenanthrene) and 1-hydroxypyrene (1-OH-pyrene), as well as cotinine and creatinine, were determined. In the exposed group, median urinary concentrations were 0.85 ?g/g creatinine for 1-OH-phenanthrene, 0.54 ?g/g creatinine for 2-/9-OH-phenanthrene, 0.99 ?g/g creatinine for 3-OH-phenanthrene, 0.22 ?g/g creatinine for 4-OH-phenanthrene, and 1.33 ?g/g creatinine for 1-OH-pyrene, all being significantly higher compared to the control group (0.55, 0.37, 0.63, 0.11 and 0.54 ?g/g creatinine, respectively). Using a multivariate linear regression analysis including sex, cotinine and tobacco smoking as covariates, exposure to e-waste recycling activities was the most important determinant for PAH exposure. On physical examination, pathological findings were rare, but about two thirds of exposed individuals complained about cough, and one quarter about chest pain. In conclusion, we observed significantly higher urinary PAH metabolite concentrations in individuals who were exposed to e-waste recycling compared to controls who were not exposed to e-waste recycling activities. The impact of e-waste recycling on exposure to environmental toxins and health of individuals living in the surroundings of e-waste recycling sites warrant further investigation.
EVALuna2:9705